The continuous fiber networks with a balanced bimodal orientation of P(NDI2OD-T2) by controlling solution nucleation and face-on and edge-on crystallization rates. (2nd December 2022) - Wang, Sichun; Zhang, Tao; Zhang, Lu; Liu, Duo; Liu, Xinyu; Li, Junhang; Li, Hongxiang; Zhang, Qiang; Han, Yanchun
Abstract: The conjugated semiconducting polymer film morphology with long fiber and optimizing molecular packing is strongly correlated with charge transport properties. Herein, we report a method to obtain continuous fiber networks with a balanced bimodal orientation of poly[N, N′-bis(2-octyldodecyl)-naphthalene-1, 4, 5, 8-bis(dicarboximide)-2, 6-diyl]-alt-5, 5′-(2, 2′-bithiophene) [P(NDI2OD-T2)] thin films by controlling solution nucleation and edge-on and face-on crystallization rates. This is enabled by adding ethylene glycol (EG) (the optimal content is 3 vol%) to P(NDI2OD-T2) in chloroform solution which improves the polarization of the NDI2OD units along the backbone direction and solution pre-aggregation. Therefore, the crystal nuclei are formed in solution state during the three-phase line receding as characterized by in situ polarized optical microscopy. Moreover, the peak intensity of the aggregated state increases with solvent evaporation, illustrating that the nucleation and crystal growth proceed simultaneously in the drying process as revealed by in situ ultraviolet–visible absorption spectra. The film morphology of continuous fibrous networks with an average fiber length of 531 nm is formed. In addition, the slopes of (100) peak area vs time in the out-of-plane and in-plane directions are similar, indicating that the edge-on and face-on crystallization rates are almost equal as obtained from in situ grazing incidence wide-angle X-ray scattering. Thus, the bimodal orientation with an edge-on and face-on mixing ratio is approximately 1. The average electron mobility of the field effect transistors of P(NDI2OD-T2) films with this continuous fiber network reaches to 0.2 cm 2 V −1 s −1, an almost 3-fold improvement compared with devices without EG addition films. Graphical abstract: Image 1 Highlights: Investigated the solution nucleation and crystal growth of P(NDI2OD-T2). Reported the equal crystallization rates of edge-on and face-on orientation. Obtained the continuous fiber morphology and a balanced bimodal orientation.